A Digital-based Talent Acquisition Framework for Start-ups: A Qualitative Multiple Case Study - Mohammad Hosein Kenarroodi; Hasan Boudlaie (‫مدیریت بازرگانی)
Objective Talent acquisition for start-up businesses is a crucial concept that can lead to several significant problems such as market share decline if overlooked. The situation worsens when start-up businesses decide to keep pace with digital developments and start incorporating digitalization into their talent acquisition strategies. For this purpose, the current research sought to provide a framework for talent acquisition in start-up businesses, focusing on talent recruitment, selection, and onboarding in the digital platform.